Low Concentrations of Chlorhexidine Inhibit the Formation and Structural Integrity of Enzyme-Treated Multispecies Oral Biofilms - Gränicher, Kay Andrin; Karygianni, Lamprini; Attin, Thomas; Thurnheer, Thomas (Frontiers in Microbiology, 2021)
The self-produced matrix of biofilms, consisting of extracellular polymeric substances, plays an important role in biofilm adhesion to surfaces and the structural integrity of biofilms. In dentistry, biofilms cause multiple diseases such as caries, periodontitis, and pulpitis. Disruption of these biofilms adhering to dental hard tissues may pose a major challenge since biofilms show higher tolerance to antimicrobials and antibiotics than planktonic cells. In this study, the effect of low concentrations of chlorhexidine (CHX) on enzyme-treated multispecies oral biofilm was investigated in an in vitro model. Six-species biofilms were enzymatically treated by anaerobic growth in a medium containing DNase I and proteinase K. Biofilms were exposed to a low concentration of CHX at defined time points. After 64 h, biofilms were either harvested and quantified by cultural analyses or stained for confocal laser scanning microscopy (CLSM) analyses using either Live/Dead kit or different fluorescent dyes. A mixture of YoPro1 and SYTOX™ Green, Fluorescent Brightener 28 (Calcofluor), and SYPRO™ Ruby Protein Gel Stain were used to stain total DNA, exopolysaccharides, and extracellular proteins, respectively. Extracellular DNA (eDNA) was visualized via an indirect immunofluorescence assay (Mouse anti-DNA IgG, Goat anti-Mouse IgG, Streptavidin-Cy3). Overall, the total colony-forming units (CFUs) significantly decreased after combined treatment with a low concentration of CHX and enzymes compared to the group treated with CHX alone (p < 0.001). These findings also apply to five species individually (Streptococcus mutans, Streptococcus oralis, Actinomyces oris, Veillonella dispar and Candida albicans) occurring in the biofilms, with Fusobacterium nucleatum being the only exception. Furthermore, CLSM images showed less dense biofilms and a reduction in cell numbers after combined treatment compared to the group without enzymes. The combination of enzymes capable of disturbing the matrix integrity with antimicrobial agents thus appears to be a promising approach for biofilm disruption and killing.